Multimedia Pembelajaran Interaktif Perangkat Keras Komputer Berbasis AR DI SMK Muhammadiyah Pagar Alam - Nanda S Prawira (PPPM Institut Teknologi Pagar Alam, 2026)
This study aims to develop and evaluate interactive Augmented Reality-based learning multimedia for computer hardware topics at SMK Muhammadiyah Pagar Alam. The initial problems include the dominant use of two-dimensional images, limited practice equipment, and students’ difficulty in understanding the form, function, and relationship of computer components. The study applied a Research and Development approach using the Multimedia Development Life Cycle model, which consists of concept, design, material collecting, assembly, testing, and distribution. The trial involved 30 students. Data were collected through observations, interviews, expert validation sheets, black-box testing, student response questionnaires, and pretest-posttest assessments. The simulated results showed media feasibility of 92.50%, material feasibility of 90.00%, functional testing success of 100%, and student response of 88.47%. The average score increased from 56.13 in the pretest to 84.70 in the posttest. The class N-Gain score was 0.65, which was categorized as moderate, while learning mastery increased from 0% to 93.33%. The paired-samples t-test produced t = 33.219 with p < 0.001, indicating a significant difference between learning outcomes before and after using the media. These findings indicate that the developed media is feasible, practical, and potentially effective in improving students’ understanding of computer hardware. Future studies should involve a control group, a larger sample, and learning retention measurements.